Christ-centered therapy : empowering the self - Harris, Russ, 1938- (Haworth religion and mental health., 2002)
Help your clients gain access to the transformative grace of God through Christ!All too often, psychology and spirituality are kept in separate boxes, lessening the power of each to work effective changes. Christ-Centered Therapy: Empowering the Self brings together Christian faith with the Internal Family System (IFS) model. This widely accepted paradigm facilitates psychological healing by showing how the self can become the change agent for the dysfunctional internal system. Christ-centered IFS (CCIFS) combines the power of internal system therapy with the healing power of God f.